Stress modification in gold metal thin films during thermal annealing - Prószyński, Adam; Chocyk, Dariusz; Gładyszewski, Grzegorz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Stress evolution during deposition of 50 nm Au thin films by thermal evaporation in a UHV system and then stress modification during thermal vacuum annealing have been performed. For stress measurement a substrate curvature approach has been applied. The changes in stress versus temperature linked to a modification of microstructure has been interpreted. To obtain any information about structural changes in the film X-ray diffraction measurements has been performed. We can conclude from the measurements that during the first cycle some irreversible structural modifications occur in a metal film.
Optica Applicata, Vol. 39, 2009, nr 4, s. 705-710
Keywords: optyka; thin films; annealing; strain; stress